Effect of Land-Use Intensification on Soil Properties and Plant Species Diversity in the Mediterranean Agroecosystem - Anastasios ZOTOS; Vassilios TRIANTAFYLLIDIS; Chariklia KOSMA; Ioanna KAKABOUKI; Ioannis ROUSSIS; Antonios MAVROEIDIS; Panteleimon STAVROPOULOS; Dimitrios BILALIS (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2023)
In recent decades, agriculture in Greece has undergone significant changes due to the intensification of land use. This intensification, contrary to the sustainable land management, has an impact on the healthiness of the environmental agroecosystem. This study aimed to investigate if these cultivation systems influence some of the main edaphic properties and plant species diversity and which are the main anthropogenic interventions which may have a decisive role in the changes of soil physicochemical properties and the reduction of plant species. To assess the environmental implications among different types of land-use, the most sensitive and reliable edaphic indicators were measured and plant species diversity was recorded. Three land-use types such as maize crops, alfalafa and abandoned land were selected and ten fields with an area of approximately 1 ha in each land use type were taken. The results indicate that among the edaphic parameters pH, sand, electrical conductivity (EC), soil organic matter (SOM), NO3- as well as Ca+2 and Cu+2 soil concentration presented statistically significant differences among thirty cultivated fields. Among three different land uses, the edaphic variables EC, SOM, BD, Cal & Na concentrations presented significant differences. A higher soil organic matter content was observed in abandoned land while bulk density and electric conductivity value as well as Na+ concentrations were lower compared to other land uses. In total 122 taxa belonging to 30 families were recorded, while the families with the greatest species diversity were Poaceae, Asteraceae and Fabaceae in all land uses. Therophytes was the dominant life-form, followed by the Hemicryptophytes and Geophytes. The findings of the present study imply that different agronomic practices influence soil quality parameters, which are likely to affect species diversity and the environmental implications among different land uses.